2022
DOI: 10.1149/2754-2726/ac8438
|View full text |Cite
|
Sign up to set email alerts
|

Potentiometric Analysis of Benzalkonium Chloride with 3D Printed Ion-Selective Membranes

Abstract: Benzalkonium (BA+) chloride is one of the most common preservatives used in prescription-based and over-the-counter eye drops. Knowing the concentration of BA+ in eye drops is important for quality control (at the pharmaceutical preparation stage) and human health (ocular toxicity has been linked to BA+ use). This paper describes the design and fabrication of a benzalkonium-selective potentiometric sensor for the determination of BA+ in ophthalmic solutions. The sensor is composed of a 3D-printed ion-selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The hardness enhancement is attributed to the grain growth restriction by pinning of TiC at the grain boundary. [29][30][31][32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…The hardness enhancement is attributed to the grain growth restriction by pinning of TiC at the grain boundary. [29][30][31][32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…In another study it was found that 3D-printing offers an interesting and captivating manufacture convention for growing minimal expense sensors which could be integrated rapidly and consistently by drug organizations or local area-based drug stores. 21 Nguyen et al delineates the presentation of the electrochemical sensor which was measurably examined by the CV and DPV strategies exhibiting precision practically identical to other logical strategies also showing that MPB not entirely set in stone in beauty care products with high recuperation going from 97% to 104.3%. 22 To depict recent research progress connected with the turn of events and improvement of screen-printed terminals (SPEs).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced 3D printing and sensing technologies further improve these mechanisms' stability, contributing to energy-efficient bio-inspired robots. 37,38 However, in comparison to electrically-driven stiffening actuators, laminar jammers boast superior reaction times, minimal hysteresis, low maintenance requirements, and the capacity to generate significantly stronger resistive forces.…”
mentioning
confidence: 99%